Two new species of Neomarica (Trimezieae, Iridoideae, Iridaceae) from Southeast Brazil - Gil, André Dos Santos Bragança; Hall, Climbiê Ferreira; Koch, Ana Kelly; Bittrich, Volker; Amaral, Maria Do Carmo Estanislau Do (Phytotaxa, 2017)
Two new species of Neomarica (Trimezieae, Iridoideae, Iridaceae) from the Brazilian Atlantic Forest, Southeast Brazil, are described and illustrated: Neomarica mauroi, endemic to the municipality of Mangaratiba, Rio de Janeiro State; and Neomarica sancti-vicentei, endemic to the municipality of São Vicente, São Paulo State.